Effective chilling temperatures for dormancy release in extratropical forest trees increase from cold to warm regions - Rui Zhang; Fucheng Wang; Jinbin Zheng; Lei Chen; Hongshuang Gu; Yu Zhao; Yongshuo Fu; Yann Vitasse; Xinli Chen; Heikki Hänninen; Constantin M. Zohner; Jiasheng Wu (Proceedings of the National Academy of Sciences, 2026)
Seasonal dormancy in extratropical trees is a critical adaptation that synchronizes growth with favorable climatic conditions. Traditionally, the effective chilling temperatures (ECT) required for dormancy release have been assumed to be fixed, ranging between 0 and 10 °C, based largely on studies in cold climates. However, whether the ECT range varies across diverse climatic regions remains unclear, limiting our ability to predict tree responses to climate change. Here, we quantify ECT variation using controlled experiments on 14 species and long-term phenological observations of 65 species across a ~3,000 km latitudinal gradient in China. Our experimental results show that the estimated upper ECT threshold increases by 0.27 ± 0.06 °C per decreasing degree of latitude, indicating an expansion of the ECT range toward higher temperatures in warmer climates. Our modeling analysis of long-term phenological records supports this trend, showing a comparable increase of 0.18 ± 0.02 °C per decreasing degree of latitude. These findings provide empirical evidence of latitudinal variation in ECT, offering insights into the evolutionary adaptations in shaping tree seasonal growth across diverse climates, challenging the traditional view of a fixed 0 to 10 °C range. Incorporating this adaptive variation into vegetation models and management strategies is crucial for improving predictions of forest phenology, productivity, and resilience under climate warming.